Substructural interface force identification with limited vibration measurements - Li, Jun; Hao, H. (Springer, 2016)
This paper presents a dynamic substructural interface force identification approach with limited vibration measurements from the target substructure. The substructure is considered to be subjected to both the external excitation forces at some specific degrees-of-freedom (DOFs) within the substructure and the interface forces at interface DOFs. The interface force time histories are represented as orthogonal polynomials and their discrete Fourier transform is expressed in the matrix multiplication form which transforms the time domain interface forces into their Fourier transforms in the frequency domain. A frequency-time domain method is used to formulate the identification equation based on the relationship between two sets of response vectors in a substructure. The coefficients of orthogonal functions are identified with the Tikhonov regularization technique. Numerical studies on a seven-storey plane frame structure are conducted to investigate the accuracy and efficiency of the proposed substructure interface force identification approach.